2005
DOI: 10.1213/01.ane.0000167636.94707.d3
|View full text |Cite
|
Sign up to set email alerts
|

The Incidence of Transient Neurologic Symptoms After Spinal Anesthesia with Mepivacaine

Abstract: We prospectively evaluated 1273 patients who received spinal (or combined spinal-epidural [CSE]) anesthesia with 1.5% mepivacaine (plain, no glucose) for ambulatory surgery. We hypothesized that analysis of a large series of patients would confirm previous findings that isobaric 1.5% mepivacaine is not frequently associated with transient neurologic symptoms (TNS). Patients were contacted twice after the anesthetic, at days 1-4 and days 6-9. One-thousand-two-hundred-ten patients were successfully contacted pos… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
28
1
1

Year Published

2008
2008
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 49 publications
(32 citation statements)
references
References 21 publications
2
28
1
1
Order By: Relevance
“…Our current study extended the data collection time points to 48 and 72 hours but still did not report a patient with TNS. YaDeau et al's [14] prospective cohort study showed an overall incidence of TNS using 1.5% mepivacaine to be 6.4%; however, they noted only a 1.8% incidence of TNS among ACL reconstruction patients and were unable to explain the difference. They also found an association with age and TNS, where the average age of TNS patients was 48 ± 14 yrs versus 41 ± 16 yrs in non-TNS patients [14].…”
Section: Discussionmentioning
confidence: 96%
See 2 more Smart Citations
“…Our current study extended the data collection time points to 48 and 72 hours but still did not report a patient with TNS. YaDeau et al's [14] prospective cohort study showed an overall incidence of TNS using 1.5% mepivacaine to be 6.4%; however, they noted only a 1.8% incidence of TNS among ACL reconstruction patients and were unable to explain the difference. They also found an association with age and TNS, where the average age of TNS patients was 48 ± 14 yrs versus 41 ± 16 yrs in non-TNS patients [14].…”
Section: Discussionmentioning
confidence: 96%
“…Transient neurologic symptoms were defined as back pain or dysesthesia that radiated to the buttocks, thighs, hips or calves, using the criteria of Pollock et al [6]. Isolated back pain with point tenderness, nonradiating back pain, exacerbation of preexisting back pain, new pain in the extremities not associated with back pain, or pain at the spinal needle site was not considered to be TNS [14]. Demographic data and anesthetic and recovery parameters were compared using analysis of variance, t-test, and Pearson Chi-square analysis.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…In the largest observational trial to date involving 1,273 patients, the incidence of TNS with 1.5% isobaric mepivacaine was 6.4%. 31 Results from smaller randomized blinded trials have demonstrated rates of TNS ranging from 0 to 7.4%. 10,18,32,33 Reported risk factors for the development of TNS include outpatient status, obesity, lithotomy, and knee arthroscopy position.…”
Section: Discussionmentioning
confidence: 99%
“…Mepivacaine provides another option with rapid onset and relatively short duration of action; however, TNSs have been associated with 4% hyperbaric mepivacaine [20]. YaDeau et al [21] studied isobaric 1.5% mepivacaine in patients undergoing orthopedic lower limb surgery. Intrathecal doses of 45-50 mg produced excellent anesthesia for lower limb procedures of less than 90 min duration with combined spinal epidural (CSE) techniques preferred for surgery of longer than 90 min expected duration.…”
Section: Short-acting Agentsmentioning
confidence: 99%